EFL Practicum Realities: Challenges Shaping Preservice Teachers' Professional Development - Asrida, Deni; Syamsudarni, Syamsudarni; Marwan, Syaiful (UNIB Press, 2025)
This research aims to discover the experiences of preservice English teachers during their teaching practice in Islamic state universities in West Sumatera Province, Indonesia and the unique difficulties they face. Using a descriptive quantitative design, the researchers gathered data from 150 respondents through the questionnaires in five primary areas: linguistic challenges, teaching difficulties, mentorship and supervision, school support, and school culture. Evidence collected during the research detailed that participants 72% could not explain their lessons in English, and classroom talk was identified to be a significant barrier 68%. Students also experienced difficulties in pedagogy, with respondents reporting low confidence in the use of diverse teaching strategies 61% and a lack of confidence 66% in the use of technology in teaching. In terms of supervision, 70% of respondents did not receive sufficient feedback from their mentors, and 63% of respondents described the lack of dialogues and discussions on teaching and learning strategies. Respondents also described their school as having little support and supervision. Other challenges respondents described included lack of internet 75% and their school was also described as remote (62%). In the area of organizational culture, respondents 78% remarked that the teaching practice was too brief to establish relationships with the teachers, and 67% described the work environment as having little to no participation. These findings highlight significant gaps in language proficiency, pedagogical preparedness, quality of mentoring and institutional coordination which significantly impact the professional growth of preservice teachers.